MEDIATING EMPIRE;AN ENGLISH FAMILY IN CHINA, 1817-1927 - Hillier, Andrew (Andrew Charles) Link (ABINGDON)
1 online resource
Keywords: As part of the growing scholarship on family and empire, this study examines Britain's presence in China through the lens of one family, arguing that, as the physical embodiment of the imperial project, it provided a social and cultural mechanism for mediating Britain's imperial power, authority and presence, and forging connections and networks throughout the expanding British world. Drawing on public and private papers, it breaks significant new ground in its development of those themes.